Cross-Border Acquisitions and Firm Financial Performance: The Overlooked Role of Training Investments - Saeed, Abubakr; Kolev, Kalin D.; Hussain, Tanveer; Pichler, Shaun; Malik, Omer Farooq (John Wiley & Sons, 2026)
Cross-border acquisitions involving developed and emerging economies serve as an important source of organizational learning and performance renewal. Yet, how these cross-border learning opportunities are internalized through human capital investment and how such investments influence post-acquisition outcomes remain a theoretically rich but empirically underexplored question. Based on the resource-based view of the firm and, in conjunction, the absorptive capacity literature, we propose that acquisitions between firms from different economic categories (developed vs. emerging economies) have a positive effect on the training investments, which, in turn, positively mediates the effect of cross-border acquisitions on post-acquisition firm performance. We further propose firm-specific contingencies that bound the relationships between cross-border acquisitions, training investments, and firm performance. Specifically, we argue that acquirers with prior experience are less reliant on training investments, and R&D of the acquired firm plays a complementary role to training investments in generating higher returns from the acquisition. We test these propositions using data on 1759 acquisition deals during the period 2004–2023. Our results provide support for our theoretical arguments. The findings advance the human resource management literature by highlighting the capability-building role of training in leveraging human capital to enhance firm performance in cross-border acquisitions. The study also has practical implications for multinational acquirers aiming to strengthen organizational capabilities and build post-acquisition resilience through targeted training investments.
Keywords: Cross-border acquisition; Training investment; Firm performance; Emerging economies; Developed economies; fi=Rahoitus|en=Finance|